Poznańska leksyka regionalna w świetle koncepcji geografii myślenia Richarda E. Nisbetta - Piotrowicz, Anna; Witaszek-Samborska, Małgorzata (Investigationes Linguisticae, 2013)
This article is an attempt to use the Richard Nisbett’s observations (the differences in the structure of parts of speech in the languages of East and West) to the Polish language and Poznań regional vocabulary. The analysis applies only to the lexical system, rather than the structure of words in texts. Studies confirm that the Polish language lexical system - both general and regional - is close to the languages of the West.